HUBUNGAN KUALITAS PELAYANAN INFORMASI DENGAN TINGKAT KEPUASAN PENGUNJUNG DI GEOPARK INFORMATION CENTER PALABUHANRATU - Danu Triana; Qoute Nuraini; Ismail Taufik Rusfien (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
The aim of this research is to determine the characteristics of visitors. Finding the effective communication is delivered by the Geopark Information Center office in conveying information to visitors who come to the office. The formulation of the problem that arises in this research is to know how the Relationship between Information Services and Visitor Satisfaction Level at Palabuhanratu Geopark Information Center (GIC). As well as wanting to find out how strong is the real relationship between the service relations carried out by the GIC office with the satisfaction of visitors who come to the Geopark Information Center office.The results of this studyshows that the Relationship between the Quality of Information Services with the Level of Visitor Satisfaction at the Geopark Information Center were effective.Keywords: Palabuhanratu Geopark Information center (GIC); the quality of information services; visitor satisfaction level;.